Effects of Nitrogen Management on Soil Nitrogen Content and Rice Grain Yield in Double Cropping Rice Production Area with Continuous Full Amount of Straw Returning. Issue 20 (13th November 2019) - Ju, Jing; Cai, Yixiang; Zuo, Wengang; Hai-Tao, Zhao; Yang, Hongjian; Mao, Wei; Yu-Hua, Shan; Ke, Feng
ABSTRACT: In order to formulate a nitrogen (N) management strategy under continuous full amount of straw returning (CFSR) for double cropping rice production, long-term (2013–2016) paddy field experiments were conducted in double cropping rice production area in the Jiangxi province, China. Five N fertilizer treatments under CFSR were tested, that is, (i) no N fertilizer application (CK); (ii) conventional N fertilizer application (165kg N ha −1 and 195 kg N ha −1 in early and late rice variety with the ratio of basal dressing to topdressing as 6:4, respectively) (CNF6:4 ); (iii) recommended N fertilizer application (135 kg ha −1 N and 165 kg ha −1 N in early and late rice variety with the ratio of basal dressing to topdressing as 4:6, 6:4, and 8:2, respectively) (RNF4:6, RNF6:4, and RNF8:2 ). Nitrogen fertilizer treatments under CFSR had 5.70% and 8.93% higher soil total nitrogen (TN), 1.32% and 0.80% higher available nitrogen (AN), 16.55% and 22.94% higher NH4 + -N, and 13.10% and 7.93% higher NO3 - -N than CK treatments in early and late rice variety, respectively. There were no differences in soil TN, AN, NH4 + -N, and NO3 - -N contents between CNF6:4 and RNF6:4 treatments, while CNF6:4 treatment showed higher or significantly higher soil N contents than RNF4:6 and RNF8:2 treatments. N fertilizer treatment under CFSR showed 88.9% and 43.20% higher grain yield and 62.15% and 42.52% higher panicle numbers than CK treatments in early and late rice variety, respectively. Compared with CNF6:4, RNF treatments did not significantly reduce grain yield and yield components in early and late rice variety, respectively, except for RNF8:2. Compared with RNF6:4 and 8:2, RNF4:6 showed higher rice grain yield, while no obvious differences in yield components were obtained among all RNF treatments. We concluded that N fertilizer under CFSR was helpful to improve soil N contents and double rice grain yield and panicle numbers. Appropriate reduction of N application (18% and 15% reduction in early and late rice variety, respectively) on the basis of adjusting ratio of basal dressing to topdressing as 4:6 and 6:4 did not significantly reduce soil TN and double rice grain yield and yield components, especially, the 40% basal N dressing and 60% N topdressing was beneficial to increase double rice grain yield under CFSR.